Influence of leadership, discipline and work life balance on satisfaction - Masyar, Sangkala Fajar; Muttaqin, Ridlwan; Sastri, Prinska Damara (Junal Ilmu Manajemen, 2025)
This study aims to examine the influence of leadership style, work discipline, and work-life balance on employee job satisfaction at Super Indo Cimahi. The research involved 33 employees and used a quantitative method with data collected via questionnaires. Analysis was conducted using multiple regression with SPSS 26. Results show that all three variables have a significant negative effect on job satisfaction. Regression coefficients were: leadership style (-0.358; p = 0.001), work discipline (-0.262; p = 0.002), and work-life balance (-0.578; p = 0.000). This indicates that ineffective leadership, poor discipline, and imbalance between work and life reduce employee satisfaction. The study contributes to human resource management practices by emphasizing the need for effective leadership, structured discipline, and work-life support to enhance employee well-being.